A three isolated port DC/DC converter for an energy storage system for renewable energy applications - Faruk Ahmeti; Dimitar Arnaudov; Sabrije Osmanaj (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
The use of renewable energy sources like solar photovoltaic, wind, and fuel cells is gaining popularity due to growing environmental awareness, technological advancements, and declining production costs. Power electronic converters are usually used to convert the power from renewable sources to match the load demand and grid requirements. Among these, DC–DC converters are essential for improving system functionality and power density, especially in low-voltage renewable systems that require high voltage gain. This paper presents a systematic evaluation of five advanced DC-DC converter topologies: multi-port DC, boost multiport interleaved step-up, isolated bidirectional, voltage/current fed, and general resonant focusing on their structural complexity, component count, and potential application scenarios. In addition, a novel high-gain three-port resonant A DC-DC converter is proposed, incorporating galvanic isolation via a three-winding high-frequency transformer. The converter adopts a half-bridge resonant inverter and rectifier-based load port, resulting in a compact and cost-effective solution. A detailed analysis of the converter's operation, design considerations, and control strategy is conducted using PLECS simulation. Furthermore, an experimental setup is developed to validate the converter’s practical feasibility. The setup schematic and comprehensive comparative tables are included to support the evaluation and highlight the proposed design’s capabilities.